Field Measurement of Dynamic Compressive Stress Response of Pavement-Subgrade Induced by Moving Heavy-Duty Trucks - Lingshi An; Feng Zhang; Yongchang Geng; Bo Lin (Shock and Vibration)
This paper presents the dynamic compressive stress response of pavement-subgrade induced by moving heavy-duty trucks. In order to study the distribution characteristic of dynamic pressure of pavement-subgrade in more detail, truck loadings, truck speeds, and dynamic pressure distributions at different depths were monitored under twenty-five working conditions on the section of Qiqihar-Nenjiang Highway in Heilongjiang Province, China. The effects of truck loading, truck speed, and depth on dynamic compressive stress response can be concluded as follows: (1) increasing truck loading will increase the dynamic pressure amplitude of subgrade-pavement and dominant frequencies are close to the characteristic frequencies caused by heavy-duty trucks at the speed of 70 km/h; (2) as truck speed increases, the dynamic pressure amplitudes of measuring points have an increasing tendency; the dynamic pressure spectrums are also significantly influenced by truck speed: the higher the truck speed, the wider the spectrum and the higher the dominant frequencies; (3) as depth increases, the dynamic pressure amplitudes of measuring points decrease rapidly. The influence of the front axle decreases gradually until disappearing and the compressive stress superposition phenomenon caused by rear double axles can be found with increasing depth.